Fatty liver. A health problem in type 2 diabetic patients? - Szymborska-Kajanek, Aleksandra; Wróbel, Marta; Strojek, Krzysztof (Przewodnik Lekarza/Guide for GPs, 2007)
Liver function tests are commonly used in clinical practice to screen for liver disease, monitor the progression of known disease, and monitor the effects of potentially hepatotoxic drugs. Fatty liver, regardless of cause, can lead to cirrhosis and can be an important cause of morbidity and mortality. The most common cause of abnormal liver function tests in type 2 diabetic patients is nonalcoholic fatty liver disease (NAFLD). It is frequently associated with visceral obesity, dyslipidaemia and insulin resistance, and represents another component of the metabolic syndrome. This article will provide a review of the definition, clinical symptoms and pathology of NAFLD, and drug therapy related to type 2 diabetic patients.